THE ROLE OF STAFFING AND ORIENTATION PRACTICES IN PREDICTING SERVICE-ORIENTED ORGANISATIONAL CITIZENSHIP BEHAVIOUR - Aizzat Mohd. Nasurdin; Noor Hazlina Ahmad; Cheng Ling Tan (Asian Academy of Management Journal, 2016)
This study examined the relationships between two specific human resource management practices (staffing and orientation) and service-oriented organisational citizenship behaviour. Survey data were gathered from a sample of 290 frontline employees attached to 4- and 5-star hotels in Malaysia. The partial least squares technique was used to test the research hypotheses. Results showed that staffing (consisting of recruitment and selection) and orientation have positive effects on the three dimensions of service-oriented organisational citizenship behaviours. These findings demonstrate the need for hotels to revisit their prevailing staffing and orientation practices in an attempt to enhance their employees' display of service-oriented citizenship behaviours.